OP0130 Mepolizumab for the treatment of patients with eosinophilic granulomatosis with polyangiitis: a phase iii randomised, placebo-controlled trial. (15th June 2017) - Wechsler, ME; Akuthota, P; Jayne, D; Khoury, P; Klion, A; Langford, C; Merkel, PA; Moosig, F; Specks, U; Cid, MC; Luqmani, R; Brown, J; et al.
Abstract : Background: Mepolizumab reduces blood eosinophils with concomitant clinical improvement in some hypereosinophilic syndromes and eosinophilic asthma. Objectives: To investigate the efficacy and safety of mepolizumab in patients with eosinophilic granulomatosis with polyangiitis (EGPA, Churg-Strauss). Methods: We conducted a Phase III, randomised, placebo-controlled, double-blind, parallel group, multi-centre study (NCT02020889 ) in patients with EGPA and a history of relapsing or refractory disease on stable therapy with prednisolone/prednisone ≥7.5–≤50mg/day with or without additional immunosuppressive therapy for ≥4 weeks. Patients were randomised 1:1 to receive mepolizumab 300mg or placebo subcutaneously, in addition to standard of care, every 4 weeks for 52 weeks. After Week 4, glucocorticoid dose could be tapered, per physician judgment, according to a suggested standard of care protocol. Co-primary endpoints (intent-to-treat [ITT] analysis) were accrued duration of remission (Birmingham Vasculitis Activity Score [BVAS]=0, prednisolone/prednisone dose ≤4mg/day) over 52 weeks; and the proportion of patients in remission at both Weeks 36 and 48. Secondary endpoints included average glucocorticoid dose during Weeks 49–52 and time to first EGPA relapse. Safety was also assessed. Results: The ITT population included 136 randomised patients (mepolizumab n=68, placebo n=68). Baseline characteristics were similar between groups. Duration of remission accrued over 52 weeks was significantly prolonged with mepolizumab vs placebo (odds ratio: 5.91 [95% confidence interval [CI]: 2.68, 13.03]; p<0.001); a significantly higher proportion of patients were in remission at Weeks 36 and 48 (32% vs 3%, odds ratio: 16.74 [95% CI: 3.61, 77.56]; p<0.001). Significant reductions in average daily prednisolone/prednisone dose during Weeks 49–52 were seen with mepolizumab vs placebo (odds ratio: 0.20[95% CI: 0.09, 0.41]; p<0.001). Median (range) prednisolone/prednisone dose during Weeks 49–52 was 5.0 (0.0–113.4)mg/day in the mepolizumab group and 10.0 (0.0–46.3)mg/day in the placebo group. Time to first EGPA relapse was significantly longer with mepolizumab vs placebo (hazard ratio: 0.32[95% CI: 0.21, 0.50] ;p<0.001). Rates of adverse events (AEs) and serious AEs were similar for mepolizumab and placebo. Conclusions: Treatment with mepolizumab significantly increased the likelihood and duration of remission, while reducing glucocorticoid use, in patients with EGPA, with a safety profile consistent with previous studies in severe asthma and EGPA. This demonstrates consistent and meaningful clinical benefits of mepolizumab in patients with EGPA. Acknowledgements: Funding: GSK [115921] in collaboration with NIAID [U01 AI097073] and the Division of Intramural Research, NIAID, NIH). Abstract submitted to ATS 2017. Disclosure of Interest: M. Wechsler Consultant for: Teva, AstraZeneca, BSCI, GSK, Novartis, sanofi, Vectura, Sunovion, Regeneron, Ambit bioscience, Meda, Mylan, Gliacure, Tunitas, Genentech, Theravance, Neurotronic, Sentien, P. Akuthota Grant/research support from: National Institutes of Health, Consultant for: Ambrx, Employee of: University of California San Diego, D. Jayne Grant/research support from: GSK, Consultant for: GSK, P. Khoury: None declared, A. Klion: None declared, C. Langford Grant/research support from: GlaxoSmithKline, Bristol-Myers Squibb, Genentech, P. Merkel: None declared, F. Moosig Grant/research support from: Roche, Consultant for: Roche, Chuagi, Lilly, GSK, U. Specks: None declared, M. Cid Consultant for: GSK, Novartis, Roche, Boehringer-Inhelheim, R. Luqmani Grant/research support from: Roche, GSK, Consultant for: Roche, GSK, J. Brown Shareholder of: GSK, Employee of: GSK, S. Mallett Shareholder of: GSK, Employee of: GSK, R. Philipson Employee of: Trizell Ltd, S. Yancey Shareholder of: GSK, Employee of: GSK, J. Steinfeld Shareholder of: GSK, Employee of: GSK, P. Weller: None declared, G. Gleich Shareholder of: Mutual funds, Grant/research support from: NIH, Consultant for: Genentech, Employee of: VAH, U Utah